I have a physics problem which I mostly solved, however I'm having a bit of trouble with the algebra in it. Everything is symbols so I can't speed things up by much here. I've spent quite a while trying to figure it out but (L-d) is constantly messing up my equations.
Here is the formula:
(d)(L^2)(p2)(g) + (L-d)(L^2)(p3)(g) = (p1)(L^3)(g)
and I need a formula that has d = ...
I could be way over thinking this but I don't believe I am, so any help would be appreciated.
Please note that p1, p2, and p3 are all different variables.
Here is the formula:
(d)(L^2)(p2)(g) + (L-d)(L^2)(p3)(g) = (p1)(L^3)(g)
and I need a formula that has d = ...
I could be way over thinking this but I don't believe I am, so any help would be appreciated.
Please note that p1, p2, and p3 are all different variables.
-
from the left you can pull out g and L^2 so you have
(g*L^2)(d*p2+(L-d)*p3)=p1(L^3)g
then divide the (g*L^2) from both sides.
d*p2+(L-d)*p3 = p1*L
then multiply the p3 in which gives
d*p2+L*p3-d*p3 = p1*L
then subtract L*p3 from both sides
d*p2-d*p3 = p1*L-L*p3
then pull the d out from the right.
d(p2-p3) = p1*L-L*p3
then divide both sides by (p2-p3) which leaves you with
d=(p1*L-L*p3)/(p2-p3).
then you can simplify by pulling the L out of the top.
d=(L(p1-p3))/(p2-p3)
(g*L^2)(d*p2+(L-d)*p3)=p1(L^3)g
then divide the (g*L^2) from both sides.
d*p2+(L-d)*p3 = p1*L
then multiply the p3 in which gives
d*p2+L*p3-d*p3 = p1*L
then subtract L*p3 from both sides
d*p2-d*p3 = p1*L-L*p3
then pull the d out from the right.
d(p2-p3) = p1*L-L*p3
then divide both sides by (p2-p3) which leaves you with
d=(p1*L-L*p3)/(p2-p3).
then you can simplify by pulling the L out of the top.
d=(L(p1-p3))/(p2-p3)
-
(d)(L^2)(p2)(g) + (L - d)(L^2)(p3)(g) = (p1)(L^3)(g)
Factor
(L^2)(g)((d)(p2) + (L - d)(p3)) = (p1)(L^3)(g)
(d)(p2) + (L - d)(p3) = (p1)(L^3)(g) / (L^2)(g)
(d)(p2) + (L - d)(p3) = (p1)(L)
Distribute
(d)(p2) + (L)(p3) - (d)(p3) = (p1)(L)
Factor
d(p2 - p3) + (L)(p3) = (p1)(L)
Bring over the (L)(p3)
d(p2 - p3) = (p1)(L) - (L)(p3)
d(p2 - p3) = L(p1 - p3)
Divide
d = L(p1 - p3) / (p2 - p3)
Factor
(L^2)(g)((d)(p2) + (L - d)(p3)) = (p1)(L^3)(g)
(d)(p2) + (L - d)(p3) = (p1)(L^3)(g) / (L^2)(g)
(d)(p2) + (L - d)(p3) = (p1)(L)
Distribute
(d)(p2) + (L)(p3) - (d)(p3) = (p1)(L)
Factor
d(p2 - p3) + (L)(p3) = (p1)(L)
Bring over the (L)(p3)
d(p2 - p3) = (p1)(L) - (L)(p3)
d(p2 - p3) = L(p1 - p3)
Divide
d = L(p1 - p3) / (p2 - p3)
-
(d)(L^2)(p2)(g) + (L- d)(L^2)(p3)(g) = (p1)(L^3)(g)
(d)(L^2)(p2)(g) + (L)(L^2)(p3)(g) - (d)(L^2)(p3)(g) = (p1)(L^3)(g)
(d)(g)(L^2)(p2 - p3) = (g)((p1)(L^3) - (L)(L^2)(p3))
(d) = [(g)((p1)(L^3) - (L)(L^2)(p3))] / (g)(L^2)(p2 - p3)
(d) = [(p1)(L^3) - (L)(L^2)(p3)] / (L^2)(p2 - p3)
(d) = [(p1)(L^3) - (L^3)(p3)] / (L^2)(p2 - p3)
(d) = [(L^3)((p1) - (p3))] / (L^2)(p2 - p3)
(d) = [(L)((p1) - (p3))] / (p2 - p3)
(d)(L^2)(p2)(g) + (L)(L^2)(p3)(g) - (d)(L^2)(p3)(g) = (p1)(L^3)(g)
(d)(g)(L^2)(p2 - p3) = (g)((p1)(L^3) - (L)(L^2)(p3))
(d) = [(g)((p1)(L^3) - (L)(L^2)(p3))] / (g)(L^2)(p2 - p3)
(d) = [(p1)(L^3) - (L)(L^2)(p3)] / (L^2)(p2 - p3)
(d) = [(p1)(L^3) - (L^3)(p3)] / (L^2)(p2 - p3)
(d) = [(L^3)((p1) - (p3))] / (L^2)(p2 - p3)
(d) = [(L)((p1) - (p3))] / (p2 - p3)